Interaksi Sistem Imun dan Hematologi dalam Mekanisme Pertahanan Tubuh: Tinjauan Imunobiologi - Hilya Saputri; Syalwa Arsa; Firdus Firdus; Rosnizar Rosnizar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The immune system and the hematological system are closely interconnected biological systems that play essential roles in maintaining homeostasis and protecting the body against pathogens. This study aimed to comprehensively examine the interaction between the immune and hematological systems from an immunobiological perspective. The study employed a literature review method by analyzing scientific articles published between 2015 and 2025 from national and international journals. The findings indicate that leukocytes, platelets, erythrocytes, and plasma components contribute significantly to immune regulation and defense mechanisms. Cellular interactions involving immune cells, inflammatory mediators, and hematopoietic processes facilitate coordinated responses to infection and tissue injury. Platelets participate in immune signaling and inflammation, while erythrocytes contribute to immune modulation through complement interactions and inflammatory regulation. Furthermore, hematological parameters can serve as important indicators of immune responses in infectious and inflammatory diseases. Overall, the integration of immune and hematological systems is crucial for maintaining physiological balance and supporting effective host defense mechanisms. Understanding this relationship may contribute to the development of improved diagnostic, prognostic, and therapeutic strategies for various diseases.